Derivado da Licarina A como potente agente leishmanicida: efeito no potencial de membrana mitocondrial - Alves, Marcilene Aparecida (2021)
Leishmaniasis combined a diverse set of parasitic diseases caused by flagellated protozoa of the genus Leishmania. The therapeutic options available are scarce, of high cost and high toxicity, have adverse effects, parasitic resistance and recurrence. Natural compounds and their candidates are considered candidates for pharmaceutical candidates to study pathologies. Among the natural compounds with known leishmanicidal activity, however, little studied, is the neolignan Licarin A. The present study aimed to analyze the leishmanicidal activity of Licarina A (DL01) and 17 of its derivatives in both evolutionary forms of Leishmania (L.) amazonensis, as well as its cytotoxicity and possible mechanisms of action. For this, promastigote forms (10 6 cells / mL) were treated with the compounds in different concentrations (0.1 to 40 µg / mL) and incubated for 72 hours at 25 ° C. After this period, cell viability was assessed by the resazurin method to determine the inhibitory concentration of 50% of the cells (IC 50 ). Cytotoxicity was determined in murine peritoneal macrophages (10 6 cells / mL) treated with compounds in different concentrations (3.9 to 500 µg / mL) and incubated for 48 hours at 37 ° C, 5% CO 2 . Cell viability was determined by the MTT [3 (4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide] for the determination of the 50% cytotoxic concentration (CC 50 ). In addition, the compounds that showed the best selectivity indexes (IS) were subjected to the evaluation of anti-amastigote activity, in which macrophages (5x10 5 cells / mL) were infected with promastigote forms in the stationary phase of the proliferation curve, treated for 48 hours with the compounds on a concentration scale (0.1 to 40 µg / mL), stained with giemsa and analyzed under an optical microscope. Then, the best IS obtained in relation to the amastigote forms was used to select the most promising compound for the study of the mechanism of action. This was done through the analysis of the mitochondrial membrane potential (ΔΨ) using the JC-10 probe. The results indicated that thirteen of the studied compounds showed activity against the promastigote forms, some of which were less toxic compared to the compound DL01 and Amphoterin B. The compounds DL03, DL10, DL17 and DL21 showed higher IS in relation to the promastigote forms, varying between 1.9 to 7.54. When submitted to anti-amastigote analysis, the DL21 compound showed better activity among the other tested compounds (IC50 = 0.45 ± 0.07 g / mL) and with higher IS, 41.1. Thus, DL21 was selected for the study of mechanism of action, together with DL01. Given the effects of these compounds on ΔΨ, DL01 reduced it by 13.5%, while DL21 increased it by 3.0%. The results obtained indicate that the compound DL21 is a promising drug candidate with leishmanicidal action. However, further studies are needed for a broader understanding of the mechanism of action, as well as in vivo assessments of activity and toxicity.